Military Activity of the Cavalry General A. M. Kaledin: Milestones in the History - Gennady Viktorovich Marchenko (North-West institute of management of the Russian Presidential Academy of National Economy and Public Administration, 2018)
The military activity of the general of Cavalry A. M. Kaledin is examined in the article. Special attention is paid to the military commanders of Novocherkassk Cossack Military School and his management environment in commanding of Russian army forces during World War I. Professional characteristics of the famous military leader and his important contribution in the development of Russian army and military education in general are revealed.